Recycling of mixed lithium-ion battery cathode materials with spent lead-acid battery electrolyte with the assistance of thermodynamic simulations. (1st September 2020) - Gu, Shuai; Zhang, Liang; Fu, Bitian; Ahn, Ji Whan; Wang, Xinpeng
Abstract: Based on the concept of recycling waste with waste, the mixed cathode materials of spent lithium-ion batteries were recycled with waste electrolyte from spent lead–acid batteries. With the assistance of thermodynamic simulations, the optimized recycling path of the mixed cathode materials was proposed and tested. A higher overall recycling ratio of valuable metals, that is, 94.9% of lithium, 94.5% of cobalt, 94.4% of nickel, and 95.5% of manganese, was achieved by replacing the oxalates/carbonates used in the precipitation process with sulfides and reducing the solubility of lithium carbonate in the lithium precipitation step at room temperature with ethanol. A higher ethanol-to-water ratio yielded a higher precipitation ratio of lithium until the ratio reached 5:1. High-purity lithium carbonate and cobalt (99.9%) were recovered as nanoparticles and nanoribbons, respectively, through precipitation using carbon dioxide in a solution with a 4:1 ethanol-to-water ratio and electrodeposition at E = −0.4 V in a traditional three-electrode system. Furthermore, the poisonous heavy metal (lead) was separated and stabilized as lead sulfide. Highlights: Waste electrolyte from spent LABs was used for leaching of LIBs. Sulfides instead of carbonates were used to precipitate Co avoided the loss of Li. High precipitation rate of Li was achieved at room temperature. Nano-sized Li2 CO3 and Co were recovered with high purity. Thermodynamic simulations were used to design the recycling path.